Discrete phase-CFD simulations of asphaltenes particles deposition from crude oil in shell and tube heat exchangers - Emani, S. (2019)
Fouling in crude preheat trains is a major cause of thermal inefficiency in petroleum refineries. The limited fundamental understanding of its causes and mechanisms led to ineffective fouling mitigation techniques. It is believed that asphaltenes precipitation and deposition is the major cause of fouling. The present work attempts to simulate the deposition of asphaltenes from crude oil in a multi-pass shell and tube heat exchanger through discrete-phase CFD simulations. The effects of bulk velocity, temperature gradients in the radial direction and particle sizes on asphaltenes deposition are investigated. In an effort to understand the effect of various forces on the rate of deposition of asphaltenes, forces such as gravity, drag, Saffman lift and thermophoretic are applied on the asphaltenes particles. The deposition velocities of the asphaltenes particles are determined based on solving the balance of these forces. The asphaltenes particles mass deposition rate is high in locations of higher particle deposition velocities. The CFD simulations indicate that the dominant forces to encourage particles deposition are gravity and drag. The deposition velocities and mass deposition rates are high for larger particle sizes. Low fluid velocities, higher temperature gradients and larger particle sizes favor higher particle deposition rates. Â© 2018 Elsevier Ltd